Predictors of Radiographic Osteoarthritis 2 to 3 Years After Anterior Cruciate Ligament Reconstruction: Data From the MOON On-site Nested Cohort. Issue 8 (30th August 2019) - ; Jones, Morgan H.; Oak, Sameer R.; Andrish, Jack T.; Brophy, Robert H.; Cox, Charles L.; Dunn, Warren R.; Flanigan, David C.; Fleming, Braden C.; Huston, Laura J.; Kaeding, Christopher C.; Kolosky, Michael; et al.
Background: Multiple studies have shown that patients are susceptible to posttraumatic osteoarthritis (PTOA) after an anterior cruciate ligament (ACL) injury, even with ACL reconstruction (ACLR). Prospective studies using multivariable analysis to identify risk factors for PTOA are lacking. Purpose/Hypothesis: This study aimed to identify baseline predictors of radiographic PTOA after ACLR at an early time point. We hypothesized that meniscal injuries and cartilage lesions would be associated with worse radiographic PTOA using the Osteoarthritis Research Society International (OARSI) atlas criteria. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 421 patients who underwent ACLR returned on-site for standardized posteroanterior semiflexed knee radiography at a minimum of 2 years after surgery. The mean age was 19.8 years, with 51.3% female patients. At baseline, data on demographics, graft type, meniscal status/treatment, and cartilage status were collected. OARSI atlas criteria were used to grade all knee radiographs. Multivariable ordinal regression models identified baseline predictors of radiographic OARSI grades at follow-up. Results: Older age (odds ratio [OR], 1.06) and higher body mass index (OR, 1.05) were statistically significantly associated with a higher OARSI grade in the medial compartment. Patients who underwent meniscal repair and partial meniscectomy had statistically significantly higher OARSI grades in the medial compartment (meniscal repair OR, 1.92; meniscectomy OR, 2.11) and in the lateral compartment (meniscal repair OR, 1.96; meniscectomy OR, 2.97). Graft type, cartilage lesions, sex, and Marx activity rating scale score had no significant association with the OARSI grade. Conclusion: Older patients with a higher body mass index who have an ACL tear with a concurrent meniscal tear requiring partial meniscectomy or meniscal repair should be advised of their increased risk of developing radiographic PTOA. Alternatively, patients with an ACL tear with an articular cartilage lesion can be reassured that they are not at an increased risk of developing early radiographic knee PTOA at 2 to 3 years after ACLR.